An integrated approach for phycoremediation of wastewater and sustainable biodiesel production by green microalgae, Scenedesmus sp. ISTGA1. (May 2019) - Tripathi, Ritu; Gupta, Asmita; Thakur, Indu Shekhar
Abstract: The present study investigates the ability of the microalgal strain Scenedesmus sp. ISTGA1 for the treatment of municipal wastewater along with biodiesel production. This strain was cultured in different concentrations of sterilized wastewater (25, 50 and 100%) with BG-11 medium for 14 days in different flasks. The physicochemical properties of wastewater were analyzed before and after algal treatment. Scenedesmus sp. ISTGA1 was able to enhance the pH (6.3 ± 0.5 to 8.3 ± 0.2) and DO (2.7 fold) of wastewater. After treatment with the algal strain ISTGA1, there was a significant removal of heavy metals and organic contaminants as analyzed by ICP-AES and GC-MS respectively. The maximum biomass and lipid production of 1.81 g/L and 452 mg/L respectively, were attained, when strain ISTGA1 was grown in 100% wastewater. A balanced mixture of saturated and unsaturated fatty acids mainly (C16 and C18) indicated an appropriate quality of biodiesel produced by the alga. The results indicated that Scenedesmus sp. ISTGA1 can be applied for phycoremediation of wastewater along with biodiesel production. Graphical abstract: Image 10635 Highlights: Scenedesmus sp. ISTGA1 assessed for wastewater treatment and biodiesel production. Nitrogen and Phosphorous was completely utilized post microalgal treatment. Reduction of heavy metal and organic contaminants was observed after treatment. Highest production of biomass and lipid observed in 100% wastewater culture. The fatty acids produced by this strain were of biodiesel quality.